2013
DOI: 10.1242/jeb.091264
|View full text |Cite
|
Sign up to set email alerts
|

Indefatigable: an erect coralline alga is highly resistant to fatigue

Abstract: SUMMARYIntertidal organisms are subjected to intense hydrodynamic forces as waves break on the shore. These repeated insults can cause a plant or animal's structural materials to fatigue and fail, even though no single force would be sufficient to break the organism. Indeed, the survivorship and maximum size of at least one species of seaweed is set by the accumulated effects of small forces rather than the catastrophic imposition of a single lethal force. One might suppose that fatigue would be especially pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Calliarthron cheilosporioides fronds were collected at Stanford University's Hopkins Marine Station (HMS) in Pacific Grove, CA, USA (36.622°N, 121.906°W), at the same lower intertidal site used in several previous studies (Martone, 2006(Martone, , 2007Martone and Denny, 2008a,b;Denny et al, 2013). Samples were held in chilled seawater (4°C) until used, usually within a day.…”
Section: Materials and Methods Sample Collectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Calliarthron cheilosporioides fronds were collected at Stanford University's Hopkins Marine Station (HMS) in Pacific Grove, CA, USA (36.622°N, 121.906°W), at the same lower intertidal site used in several previous studies (Martone, 2006(Martone, , 2007Martone and Denny, 2008a,b;Denny et al, 2013). Samples were held in chilled seawater (4°C) until used, usually within a day.…”
Section: Materials and Methods Sample Collectionmentioning
confidence: 99%
“…Tensile creep tests were performed coincidentally with the fatigue tests conducted by Denny et al (2013), and details of the apparatus can be found there. In short, a test sample (8-11 genicula) was excised from a basal section of a frond, and the cross-sectional areas of the end genicula were measured as described above.…”
Section: Tensile Creepmentioning
confidence: 99%
See 3 more Smart Citations